Divergent Antiviral Mechanisms of Two Viperin Homeologs in a Recurrent Polyploid Fish - Mou, Cheng-Yan; Li, Shun; Lu, Long-Feng; Wang, Yang; Yu, Peng; Li, Zhi; Tong, Jin-Feng; Zhang, Qi-Ya; Wang, Zhong-Wei; Zhang, Xiao-Juan; Wang, Guang-Xin; Zhou, Li; et al. (Frontiers in Immunology, 2021)
Polyploidy and subsequent diploidization provide genomic opportunities for evolutionary innovations and adaptation. The researches on duplicated gene evolutionary fates in recurrent polyploids have seriously lagged behind that in paleopolyploids with diploidized genomes. Moreover, the antiviral mechanisms of Viperin remain largely unclear in fish. Here, we elaborate the distinct antiviral mechanisms of two viperin homeologs (Cgviperin-A and Cgviperin-B) in auto-allo-hexaploid gibel carp (Carassius gibelio). First, Cgviperin-A and Cgviperin-B showed differential and biased expression patterns in gibel carp adult tissues. Subsequently, using co-immunoprecipitation (Co-IP) screening analysis, both CgViperin-A and CgViperin-B were found to interact with crucian carp (C. auratus) herpesvirus (CaHV) open reading frame 46 right (ORF46R) protein, a negative herpesvirus regulator of host interferon (IFN) production, and to promote the proteasomal degradation of ORF46R via decreasing K63-linked ubiquitination. Additionally, CgViperin-B also mediated ORF46R degradation through autophagosome pathway, which was absent in CgViperin-A. Moreover, we found that the N-terminal α-helix domain was necessary for the localization of CgViperin-A and CgViperin-B at the endoplasmic reticulum (ER) and the C-terminal domain of CgViperin-A and CgViperin-B was indispensable for the interaction with degradation of ORF46R. Therefore, the current findings clarify the divergent antiviral mechanisms of the duplicated viperin homeologs in a recurrent polyploid fish, which will shed light on the evolution of teleost duplicated genes.